Impacts of endometrioma on ovarian aging from basic science to clinical management - Tan, Zhouyurong; Gong, Xue; Li, Yiran; Hung, Sze Wan; Huang, Jin; Wang, Chi Chiu; Chung, Jacqueline Pui Wah (Frontiers in Endocrinology, 2023)
Endometriosis is a common reproductive disorder characterized by the presence of endometrial implants outside of the uterus. It affects 1 in 10 women of reproductive age. Endometriosis in the ovary, also known as endometrioma (OMA), is the most frequent implantation site and the leading cause of reproductive failure in affected women. Ovarian aging is one of the characteristic features of OMA, however its underlying mechanism yet to be determined. Accumulated evidence has shown that pelvic and local microenvironments in women with OMA are manifested, causing detrimental effects on ovarian development and functions. Whilst clinical associations of OMA with poor ovarian reserve, premature ovarian insufficiency, and early menopause have been reported. Moreover, surgical ablation, fenestration, and cystectomy of OMA can further damage the normal ovarian reservoir, and trigger hyperactivation of primordial follicles, subsequently resulting in the undesired deterioration of ovarian functions. Nevertheless, there is no effective treatment to delay or restore ovarian aging. This review comprehensively summarised the pathogenesis and study hypothesis of ovarian aging caused by OMA in order to propose potential therapeutic targets and interventions for future studies.